An Analysis of Poverty in Households Headed by Millennials in South Africa - Jabulile Lindiwe Makhalima (International Journal of Economics and Financial Issues, 2022)
Poverty is a worldwide quandary and despite global efforts to culminate it, progress in this regard has been slow and in some parts of the world, the plight has worsened. Ensuring adequate resource provision for their families and consequently evading poverty proves to be a challenge for some household heads, particularly millennials. This study therefore seeks to analyse the prevalence of poverty in households headed by millennials based on their characteristics. The study employed data from the 2021 General Household Survey of Statistics South Africa with a sample of 2685 millennial heads. The findings reveal that households headed by millennials who are males, African; single, divorced, and unemployed are vulnerable to poverty. Further findings indicate that households where the head had a tertiary qualification and was employed were less vulnerable to poverty. It can therefore be construed that head of household characteristics have a bearing on a household’s wellbeing and the future outcomes of the children in their households. Policies enacted by government needs to create realistic opportunities that will enable millennials to sustain themselves and their households.